Metal gel fiber and preparation method thereof

By mixing liquid metal gallium indium alloy with polysaccharide polymer solution and forming metal gel fibers through wet spinning technology, the problem of difficult to develop fiber materials with high electronic conductivity and excellent mechanical properties in the prior art is solved, and high-performance fiber materials suitable for flexible electronics and wearable smart fabrics are realized.

CN119843389APending Publication Date: 2025-04-18NANJING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510036407.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The prior art is difficult to develop fiber materials with high electronic conductivity and excellent mechanical properties, especially in the use of liquid metals as a continuous conductive phase.

Method used

By mixing the liquid metal gallium indium alloy with the polysaccharide polymer solution, stirring and shearing with a homogenizer to form a polymer-liquid metal mixed spinning solution, and solidifying in a solidification bath through wet spinning technology to form polymer pregel fibers. Subsequently, the solvent is removed by hot rolling treatment, and the liquid metals are connected to each other to form metal gel fibers.

Benefits of technology

It achieves high conductivity and has excellent mechanical properties, making fiber materials suitable for flexible electronics and wearable smart fabrics, expanding the application scenarios of flexible electronics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843389A_ABST
    Figure CN119843389A_ABST
Patent Text Reader

Abstract

The invention discloses a metal gel fiber and a preparation method thereof, and belongs to the field of conductive fiber preparation. The metal gel fiber comprises liquid metal and a polymer network; the liquid metal is a conductive phase of the metal gel fiber, penetrates through the polymer network and forms a continuous conductive structure; the polymer network is of a three-dimensional porous nano network structure and is uniformly distributed in the metal gel fiber. Liquid metal is added into a polysaccharide polymer solution and evenly dispersed, a polymer-liquid metal spinning solution is obtained and put into a spinning tank to be subjected to standing defoaming and solidification treatment to form polymer pre-gel fibers, the polymer pre-gel fibers are treated under a hot roller, a solvent is removed, the liquid metal is made to communicate with one another, and the metal gel fibers are obtained through a collecting roller. Compared with the prior art, the preparation method has the beneficial effects that liquid metal fluid can be fixed in a high-molecular three-dimensional nano network through electrostatic interaction, high conductivity is achieved, and meanwhile excellent mechanical performance is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive fiber preparation, and more specifically, to a metal gel fiber and a preparation method thereof. Background Art

[0002] With the rapid development of flexible electronic technology, especially the emergence of fiber electronic devices and smart textiles, it is urgent to develop a high-performance fiber material with excellent electrical and mechanical properties. The ideal fiber electrode material should perfectly combine excellent electrical and mechanical properties. In terms of electrical properties, the conductivity of the fiber must reach the metal level (>10 6 S·m-1) to ensure fast and lossless transmission of electrons, reduce power consumption and improve energy efficiency. In terms of mechanics, these fibers must be soft enough to fit the curves of the body perfectly and withstand the dynamic physical stress of daily activities, so that electronic devices can still work stably during thousands of daily physical activities.

[0003] However, existing fiber materials cannot meet the above requirements. The inherent rigidity of traditional metal wires limits their application in soft electronics. The conductivity of carbon-based fibers and intrinsically conductive polymer fibers (polyaniline, polythiophene, polypyrrole) is difficult to meet the requirements of high electrical performance. Incorporating conductive fillers into the polymer matrix may develop high-performance composite fibers. However, in the coating structure, the filler is easily detached from the fiber surface when subjected to friction, scratching or mechanical stress, affecting the stability of the electrical properties. Another type of fiber is to inject conductive materials into the fiber tube or coaxially spin and form a core-shell structure. The fiber surface is not conductive and cannot be used directly as an electrode. The most common structure is to dope conductive fillers (such as copper particles, silver nanowires, liquid metals, carbon nanotubes, etc.) in the polymer matrix, but composite fibers of this type of structure are usually difficult to form an effective and stable conductive path. And during dynamic deformation, the conductive path is easy to break, and the conductivity is usually unstable. These factors have made it impossible to achieve conductive fiber materials with both high electrical and mechanical properties.

[0004] In the related art, for example, Chinese patent document CN202311508571.1 discloses a double conductive network metal gel conductive fiber and its preparation method and application, which belongs to the field of conductive gel fiber, and includes a thermoplastic elastomer cortex, a bacterial cellulose core layer added with silver nitrate, and a double conductive network metal gel conductive fiber is prepared. Wherein, it is mainly a composite fiber with a skin-core structure prepared by introducing conductive metal particles. Another example is Chinese patent document CN115233335A discloses a flexible liquid metal / seaweed composite fiber and its preparation, which belongs to the technical field of liquid metal composite fiber preparation, and mainly involves composite spinning of liquid metal and sodium alginate, and freeze-drying to obtain composite fibers. However, the conductivity of the fiber obtained by this method is usually very low, which is difficult to meet the metal-like conductivity requirements.

[0005] From the above, it can be seen that the relevant technology has not yet provided an effective technical solution on how to use liquid metal as a continuous conductive phase to prepare fiber materials with both high electronic conductivity and excellent mechanical properties. Summary of the invention

[0006] 1. Technical problems to be solved

[0007] In response to the problem in the prior art of how to use liquid metal as a continuous conductive phase to achieve fiber materials with high electronic conductivity and mechanical properties, the present invention provides a metal gel fiber and a preparation method thereof, which can fix the liquid metal fluid in a three-dimensional nanonetwork of a polymer through electrostatic interaction, thereby achieving high conductivity while also having excellent mechanical properties.

[0008] 2. Technical solution

[0009] The purpose of the present invention is achieved through the following technical solutions.

[0010] The content of this application is used to introduce concepts in a brief form, which will be described in detail in the detailed implementation section below. The content of this application is not intended to identify the key features or essential features of the technical solution claimed for protection, nor is it intended to limit the scope of the technical solution claimed for protection.

[0011] Some embodiments of the present application provide a metal gel fiber and a preparation method thereof to solve the technical problems mentioned in the above background technology section. As a first aspect of the present application, some embodiments of the present application provide a method for preparing a metal gel fiber, comprising the following steps:

[0012] Preparation of polymer-liquid metal mixed spinning solution: adding liquid metal (gallium-indium alloy) to polysaccharide polymer solution to obtain a mixed solution, and uniformly dispersing the mixed solution with a homogenizer to obtain a polymer-liquid metal spinning solution;

[0013] Preparation of polymer pregel fiber: placing the polymer-liquid metal spinning solution in a spinning tank and letting it stand to defoam, and then passing through a wet spinning machine through a spinneret into a coagulation bath at room temperature for coagulation to form a polymer pregel fiber;

[0014] Post-treatment of polymer pre-gel fiber: The polymer pre-gel fiber is treated under a hot roller to remove the solvent and make the liquid metal interconnected, and the metal gel fiber is obtained by a collecting roller.

[0015] Furthermore, the polymer-liquid metal mixed spinning solution is ultrasonically dispersed into nano-microsphere droplets dispersed in the polymer aqueous solution, and the polymer chains form a physically cross-linked network that is adsorbed on the surface of the liquid metal to form a microgel shell; the polymer undergoes coordination and solidification in the coagulation bath, and the microsphere droplets are fixed in the polymer network.

[0016] Furthermore, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0017] Furthermore, the step of preparing the fucoidan-liquid metal spinning solution is: mixing the liquid metal gallium-indium alloy with 1wt% to 3wt% of the fucoidan solution in a weight ratio of (6:4) to (9:1) to obtain a first mixed solution;

[0018] The first mixed solution was stirred and sheared at a temperature of 25° C. using a handheld homogenizer at a speed of 8000 rpm to 15000 rpm for 5 to 10 minutes to obtain a fucoidan-liquid metal spinning solution.

[0019] Furthermore, the step of preparing the sodium alginate-liquid metal spinning solution is: mixing the liquid metal gallium-indium alloy with 1wt% to 3wt% of the sodium alginate solution in a weight ratio of (6:4) to (9:1) to obtain a second mixed solution;

[0020] The second mixed solution was stirred and sheared for 5 to 10 minutes at a speed of 8000 to 15000 rpm using a handheld homogenizer at a temperature of 25° C. to obtain a sodium alginate-liquid metal spinning solution.

[0021] Furthermore, the preparation of polymer pregel fibers includes the preparation of fucoidan pregel fibers and the preparation of sodium alginate pregel fibers.

[0022] Furthermore, the steps for preparing fucoidan pregel fibers are as follows: placing the fucoidan-liquid metal spinning solution into a spinning tank and letting it stand to defoam, and the spinning solution passes through a wet spinning machine through a spinneret and enters a 0.01M calcium chloride coagulation bath at room temperature to coagulate, thereby forming fucoidan pregel fibers.

[0023] Furthermore, the steps for preparing sodium alginate pregel fibers are as follows: placing the sodium alginate-liquid metal spinning solution into a spinning tank for standing and defoaming, and the spinning solution passes through a wet spinning machine through a spinneret and enters a 0.01M calcium chloride coagulation bath at room temperature for coagulation to form sodium alginate pregel fibers.

[0024] Furthermore, during the post-treatment of the polymer pregel fiber, the polymer pregel fiber is repeatedly rolled by a hot roller for three times, and the ambient temperature of the hot roller is 20°C to 80°C.

[0025] As the second aspect of the present application, some embodiments of the present application provide a metal gel fiber, comprising liquid metal and a polymer network; the liquid metal is the conductive phase of the metal gel fiber, which runs through the polymer network and forms a continuous conductive structure; the polymer network is a three-dimensional porous nano-network structure, which is evenly distributed in the metal gel fiber.

[0026] 3. Beneficial effects

[0027] Compared with the prior art, the advantages of the present invention are:

[0028] (1) The metal gel fiber and its preparation method of the present invention develop a new fiber structure, which is designed to imitate the hydrogel structure. By replacing the fluid in the hydrogel with liquid metal, liquid metal is used as a continuous conductive phase in the fiber material for the first time;

[0029] (2) The metal gel fiber of the present invention uses a polysaccharide polymer network to design a three-dimensional polymer network skeleton in the fiber, which not only plays a role in forming a microgel shell, but also plays a role as a mechanical skeleton support;

[0030] (3) The method for preparing the metal gel fiber of the present invention can combine the dual characteristics of gel and metal to obtain a metal gel fiber that is both highly conductive and soft;

[0031] (4) Compared with the prior art in which conductive fillers are directly coated on the fiber surface, which is easy to fall off when subjected to friction or scraping, the metal gel fiber prepared by the metal gel fiber preparation method of the present invention has the advantages that the conductive phase is evenly distributed inside the fiber and has strong stability; compared with the prior art in which conductive fillers are encapsulated in polymer hollow tube fibers and conductive fibers prepared by coaxial wet spinning, the metal gel fiber of the present invention has the advantages that the fiber surface is conductive and can be directly used as an electrode; compared with the prior art in which composite fibers are prepared by doping conductive fillers, the metal gel fiber of the present invention has a fiber structure completely different from that of existing fibers, and has the advantages of high conductivity and electrical stability;

[0032] (5) The high electrical and mechanical properties of the metal gel fiber of the present invention enable it to be used in flexible wearable electronic fabrics such as sweat sensing and Joule heating, thus expanding the application scenarios of flexible electronics.

[0033] (6) The metal gel fiber of the present invention fixes the liquid metal fluid in the three-dimensional nano-network of the polymer through electrostatic interaction, achieving high electrical conductivity while also having excellent mechanical properties; the overall structural design is ingenious and the operation is simple, suitable for large-scale production and preparation; the metal gel fiber of the present invention can provide sweat sensing function and can also perform Joule heating, and can be woven into multifunctional intelligent electronic fabrics, promoting the development of flexible electronics. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 is a schematic diagram of a computer tomography image of a metal gel fiber in one embodiment of the present invention;

[0035] Figure 2 is a computer tomography image of a metal gel fiber in one embodiment of the present invention and a schematic diagram of a polymer network extracted therefrom;

[0036] Figure 3 is a schematic diagram of a SEM image of a nanoscale polymer network of a metal gel fiber in one embodiment of the present invention;

[0037] Figure 4 This is an infrared force characterization diagram of fucoidan polymer and liquid metal in fucoidan metal gel fiber in one embodiment of the present invention;

[0038] Figure 5 is a schematic diagram of the preparation process of metal gel fiber in one embodiment of the present invention;

[0039] Figure 6 This is a graph showing the variation of the electronic conductivity and Young's modulus of the fucoidan metal gel fiber with the liquid metal content in one embodiment of the present invention;

[0040] Figure 7 In one embodiment of the present invention, the fucoidan metal gel fiber is used as a sweat sensing fabric, which can stably monitor Na in the state of exercise. + , K + Real-time monitoring diagram of ions;

[0041] Figure 8 This is a diagram of the surface temperature of fabric at different heating voltages when the fucoidan metal gel fiber is used as a Joule heating material in one embodiment of the present invention;

[0042] Fig. 9 This is a performance comparison chart of the starting voltage when the fucoidan metal gel fiber is used as a Joule heating material in an embodiment of the present invention compared with other types of composite materials. DETAILED DESCRIPTION

[0043] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0044] Example 1

[0045] Combination Figures 1 to 4 The metal gel fiber of the present invention comprises liquid metal and a polymer network.

[0046] The polymer network presents a three-dimensional porous nano-network structure and is evenly distributed in the fiber. The polymer network serves as the skeleton of the fiber, and its uniform distribution inside the fiber helps to ensure the overall performance of the fiber.

[0047] Specifically, the liquid metal, as the conductive phase in the metal gel fiber, runs through the polymer network to form a continuous conductive structure. The liquid metal, as a continuum, occupies 87wt% to 98wt% of the mass fraction of the entire fiber.

[0048] The conductive phase refers to a component with conductive properties. In this embodiment, the liquid metal has good conductivity. As the conductive phase in the metal gel fiber, the fiber has electrical properties. The liquid metal is interconnected throughout the polymer network, forming a continuous channel to ensure that the current can flow freely inside the fiber, thereby significantly improving the conductive properties of the fiber. At the same time, the liquid metal has the fluidity of a liquid, and fixing it in the polymer network can still maintain the mechanical properties of the polymer.

[0049] Specifically, the polymer network and liquid metal are stably fixed via electrostatic interactions.

[0050] Electrostatic interaction refers to the attractive or repulsive force generated by charge distribution. In this embodiment, the polymer network and the liquid metal can maintain the structural stability and electromechanical performance stability of the fiber through electrostatic interaction.

[0051] More specifically, the polymer network in the fiber presents a three-dimensional porous structure at the nanoscale, which serves as the mechanical support of the entire structure and provides the metal gel fiber with excellent mechanical properties with adjustable mechanical properties. The liquid metal is stably fixed in the entire polymer network through interaction, forming a uniform and continuous conductive phase, which provides the metal gel fiber with high electronic conductivity, and the continuous conductive phase and internal electrostatic interaction provide the fiber with stability of electromechanical properties under various deformation conditions.

[0052] Among them, the three-dimensional porous structure presenting nanoscale refers to the existence of a structure with nanoscale size, three-dimensional spatial distribution and many small holes inside in the polymer network. This structure provides a large number of action sites and mechanical support for the material, which is conducive to enhancing the mechanical properties and conductivity of the material.

[0053] The nanoscale three-dimensional porous structure is part of the polymer network. The small holes and connecting parts inside it together constitute the skeleton of the material, providing the necessary strength and stability for the entire material. This structure can effectively disperse external forces and prevent the material from breaking or deforming when subjected to force, thus serving as the mechanical support for the entire structure. In addition, the mechanical properties of the metal gel fiber can be adjusted by changing the composition, structure or type of liquid metal of the polymer network.

[0054] In a specific embodiment, the metal gel fiber forms two systems according to the types of liquid metal and polymer network used: fucoidan-gallium-indium alloy metal gel fiber and sodium alginate-gallium-indium alloy metal gel fiber. The electronic conductivity of these two metal gel fibers exceeds 2.00×10 6 S·m -1 The main difference between these two types of metal gel fibers is that they use different polymer networks, which give them unique mechanical and electrical properties.

[0055] The metal gel fiber of this scheme is a new type of fiber material. This fiber has broad application prospects in fiber electronic devices and wearable smart fabrics, and can be used in cutting-edge technology fields such as sweat monitoring and high-joule heating.

[0056] Specifically, fucoidan-gallium-indium alloy metal gel fiber, as an excellent sensing monitoring material, can stably monitor Na under dynamic operation due to its high electrical conductivity and stability under deformation. + , K + ions, reflecting the physiological health status of the human body; in addition, thanks to the high electrical conductivity and high mechanical properties of fucoidan-gallium-indium alloy metal gel fiber, fucoidan-gallium-indium alloy metal gel fiber is a stable Joule heating material with low voltage drive. After being woven into fabric, the driving voltage of 0.15V to 0.90V can increase the temperature of the fabric surface by 17℃ to 66℃, and the heating performance is stable before and after 1000 bending deformations. Compared with the heating fabric prepared by composite conductive fibers reported in the literature, fucoidan-gallium-indium alloy metal gel fiber can drive the fabric surface temperature to increase by 40℃ at a relatively low voltage of 0.6V, which has the potential to reduce the power consumption of wearable electronic devices.

[0057] The fiber material with a new structure proposed in the present invention, namely metal gel fiber, overcomes the limitations of the existing technology and realizes that liquid metal is stably fixed in the three-dimensional nanostructured fucoidan network rich in sulfonic acid groups through electrostatic interaction. This unique structure gives the fiber both metal-level conductivity and skin-like softness, while maintaining stable electromechanical coupling performance under various types of cyclic deformation.

[0058] Example 2

[0059] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0060] Preparation of polymer-liquid metal mixed spinning solution:

[0061] Liquid metal is added into a polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0062] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0063] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0064] Preparation of fucoidan-liquid metal spinning solution:

[0065] Mixing a liquid metal gallium-indium alloy with 1 wt% to 3 wt% of a fucoidan solution in a weight ratio of (6:4) to (9:1) to obtain a first mixed solution;

[0066] The first mixed solution is stirred and sheared at a speed of 8000 rpm to 15000 rpm for 5 to 10 minutes using a handheld homogenizer at a temperature of 25° C. to obtain a fucoidan-liquid metal spinning solution;

[0067] Preparation of sodium alginate-liquid metal spinning solution:

[0068] Mixing a liquid metal gallium-indium alloy with 1 wt% to 3 wt% of a sodium alginate solution in a weight ratio of (6:4) to (9:1) to obtain a second mixed solution;

[0069] The second mixed solution was stirred and sheared for 5 to 10 minutes at a speed of 8000 to 15000 rpm using a handheld homogenizer at a temperature of 25° C. to obtain a sodium alginate-liquid metal spinning solution.

[0070] Specifically, wt% is weight percentage, which indicates the mass proportion of a certain component in a mixture; RPM is the number of revolutions of an object per minute.

[0071] More specifically, the polymer-liquid metal mixed spinning solution prepared in this step is ultrasonically dispersed into nano-microsphere droplets dispersed in the polymer aqueous solution by a homogenizer, and the entangled polymer chains form a physically cross-linked network that is adsorbed on the surface of the liquid metal to form a microgel shell.

[0072] Preparation of polymer pregel fibers:

[0073] The prepared polymer-liquid metal spinning solution is placed in a spinning tank for static defoaming, and the spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath at room temperature for coagulation to form a polymer pregel fiber. The preparation of the polymer pregel fiber includes the preparation of fucoidan pregel fiber and the preparation of sodium alginate pregel fiber.

[0074] In a specific embodiment, the process of preparing the polymer pregel fiber is as follows:

[0075] Preparation of fucoidan pregel fibers:

[0076] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret and enters a 0.01M calcium chloride coagulation bath at room temperature to coagulate, thereby forming fucoidan pregel fibers.

[0077] Preparation of sodium alginate pregel fibers:

[0078] The sodium alginate-liquid metal spinning solution is sucked into a spinning tank and placed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret and enters a 0.01M calcium chloride coagulation bath at room temperature to coagulate, thereby forming a sodium alginate pregel fiber.

[0079] Specifically, the polymer in this step is coordinated and solidified in the coagulation bath, and the microsphere droplets are fixed in the polymer network. The polymer refers to the main components of the spinning solution, namely fucoidan and sodium alginate.

[0080] M stands for molar concentration; coagulation in a coagulation bath refers to the process in which, in the process of manufacturing chemical fibers, the spinning colloid solution passes through the spinneret and enters the coagulation bath and coagulates or undergoes chemical changes to form fibers; static defoaming refers to allowing the spinning solution to stand in the spinning tank for a period of time before spinning. The purpose of static defoaming is to allow the bubbles in the solution to gradually rise to the surface and burst, thereby eliminating the bubbles in the solution.

[0081] Post-treatment of polymer pre-gel fibers:

[0082] The polymer pre-gel fiber is slowly processed under a hot roller, and the liquid metal is interconnected while the solvent is removed, and the metal gel fiber is obtained by a collecting roller.

[0083] Herein, slowly processing under hot rolling rollers means repeatedly rolling with hot rolling rollers, washing with water and drying.

[0084] Specifically, the prepared polymer pre-gel fiber is repeatedly rolled by a hot roller for three times, then washed and dried, and finally the obtained metal gel fiber is collected by a collecting roller.

[0085] In a specific embodiment, the ambient temperature of the hot rolling roller is 20°C to 80°C.

[0086] Among them, the hot rollers are one or more pairs of metal rollers heated to a specific temperature. The fiber material passes between the rollers and is subjected to the combined effects of pressure and heat. By heating the rollers to a specific temperature, it can ensure that the fiber is subjected to uniform and controllable heat treatment during the processing process, avoiding the degradation of fiber performance caused by overheating or insufficient cooling.

[0087] In this step, as the pre-gel fiber passes through the hot roller, the water in the pre-gel fiber is gradually removed, the polymer network becomes dense, and the microsphere droplets fixed in the polymer network break the oxide layer on the surface of the liquid metal under the action of thermal pressure, and the liquid metal flows out of the microgel layer and fuses to form an effective electronic conductive path. Finally, the liquid metal fluid becomes the main part of the fiber, forming a continuous structural phase embedded in the polymer network.

[0088] The metal gel fibers prepared according to the above steps of this scheme have excellent electrical and mechanical properties. As shown in Table 1, metal gels can be successfully prepared based on the polymer network of fucoidan and sodium alginate and liquid metal gallium indium alloy. Liquid metal accounts for the vast majority of the gel volume, and their electronic conductivity is greater than 2.00×10 6 S·m -1 , all have good mechanical properties.

[0089] Table 1 Values ​​of liquid metal content, electronic conductivity and Young's modulus of two metal gel fiber systems based on different polymer networks and liquid metals

[0090]

[0091] like Figure 6 The figure shows the variation of electronic conductivity and Young's modulus of fucoidan metal gel fiber with liquid metal content. Taking fucoidan metal gel fiber as an example, the content of liquid metal in the fiber is adjustable, and different contents can be selected according to practical applications. With the increase of liquid metal content, the conductivity of the fiber can reach 2.8×10 6 S·m -1 The Young's modulus is 1.8MPa. The electronic conductivity of the metal gel fiber reaches the metal level.

[0092] This unique fiber structure designed by fixing the liquid metal fluid phase in the polymer network gives the fiber high conductivity and softness, promoting the application of fibers in flexible electronics.

[0093] like Figure 7 As shown in Figure 2, fucoidan metal gel fibers are used as sweat sensing fabrics and can stably monitor Na during exercise. + , K + Real-time monitoring of ions. By giving breathable and comfortable everyday textiles the ability to detect multiple biomarkers in human sweat, it is a feasible way to achieve comprehensive health monitoring in daily life in the future.

[0094] At present, there are reports of biosensing fibers with good performance. However, the stress generated by the existing fiber-shaped biosensors during exercise will cause pulling on the device, which can easily cause the device signal to be unstable or even damage the device. Metal gel fibers have excellent conductivity, elastic modulus similar to that of skin, and stability under deformation. When used as sweat sensors, they can successfully record Na in the sweat of subjects during dynamic work. + and K + Changes in ion concentration.

[0095] like Figure 8 and Fig. 9 As shown, when fucoidan metal gel fiber is used as a Joule heating material, its surface temperature change diagram under different heating voltages, and its Joule heating performance and comparison with other types of fabrics reported in the literature. Maintaining thermal homeostasis is very important for personal thermal health and thermal comfort. Due to the high conductivity of metal gel fibers, the prepared fabrics can also be used for Joule heating in personal thermal management to protect individuals in cold environments from hypothermia. After the metal gel fibers are prepared into smart fabrics, they have excellent temperature regulation ability. The temperature of the fabric surface can be increased by 17°C to 66°C at a driving voltage of 0.15V to 0.90V, meeting the needs of different environmental conditions. Given the importance of operator safety, it is crucial to use a moderate driving voltage (in this embodiment, a moderate driving voltage refers to a driving voltage of less than 3V). Metal gel-based fabrics meet this requirement due to their metallic conductivity. Compared with existing fabrics made of composite conductive fibers, metal gel fabrics require much lower driving voltages to achieve a temperature rise (ΔT) of 40°C, which is critical to ensuring low power consumption and high device efficiency. This example further demonstrates that the developed new metal gel fibers have great potential in wearable smart fabrics.

[0096] Example 3

[0097] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0098] Preparation of polymer-liquid metal mixed spinning solution:

[0099] Liquid metal is added into a polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0100] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0101] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0102] Preparation of fucoidan-liquid metal spinning solution:

[0103] Mixing a liquid metal gallium-indium alloy with a 2 wt % fucoidan solution at a weight ratio of 6:4 to obtain a first mixed solution;

[0104] The first mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a fucoidan-liquid metal spinning solution;

[0105] Preparation of sodium alginate-liquid metal spinning solution:

[0106] Mixing the liquid metal gallium-indium alloy with 2 wt % sodium alginate solution at a weight ratio of 6:4 to obtain a second mixed solution;

[0107] The second mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a sodium alginate-liquid metal spinning solution.

[0108] Specifically, the polymer-liquid metal mixed spinning solution prepared in this step, after undergoing high-speed stirring and shearing in a homogenizer, forms nano-scale droplets dispersed in the solution, and the polymer network is dispersed on the metal surface and in the solution.

[0109] Preparation of polymer pregel fibers:

[0110] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0111] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0112] Here, mm / min indicates the number of millimeters moved or changed per minute.

[0113] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0114] Post-treatment of polymer pre-gel fibers:

[0115] The prepared fucoidan pregel fiber was repeatedly rolled three times by a hot rolling roller, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0116] The prepared fucoidan pregel fiber was repeatedly rolled three times by a hot rolling roller, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0117] In a specific embodiment, the ambient temperature of the hot rolling roller is 60°C.

[0118] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0119] Compared with the composite fibers prepared by doping conductive fillers in the prior art, the metal gel fibers prepared by the metal gel fiber preparation method of the present scheme have a fiber structure completely different from the existing fibers, and have the advantages of high electrical conductivity and electrical stability.

[0120] Example 4

[0121] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0122] Preparation of polymer-liquid metal mixed spinning solution:

[0123] Liquid metal is added into a polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0124] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0125] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0126] Preparation of fucoidan-liquid metal spinning solution:

[0127] Mixing a liquid metal gallium-indium alloy with a 2 wt % fucoidan solution at a weight ratio of 7:3 to obtain a first mixed solution;

[0128] The first mixed solution was stirred and sheared at a temperature of 25° C. using a handheld homogenizer at a speed of 15,000 rpm for 5 to 10 minutes to obtain a fucoidan-liquid metal spinning solution;

[0129] Preparation of sodium alginate-liquid metal spinning solution:

[0130] Mixing the liquid metal gallium-indium alloy with 2 wt % sodium alginate solution at a weight ratio of 7:3 to obtain a second mixed solution;

[0131] The second mixed solution was stirred and sheared at a temperature of 25° C. using a handheld homogenizer at a speed of 15000 rpm for 5 to 10 minutes to obtain a sodium alginate-liquid metal spinning solution.

[0132] Specifically, in this step, the liquid metal undergoes high-speed stirring and shearing in a homogenizer, forming nano-scale droplets dispersed in the solution, and a polymer network dispersed on the metal surface and in the solution.

[0133] Preparation of polymer pregel fibers:

[0134] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0135] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0136] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0137] Post-treatment of polymer pre-gel fibers:

[0138] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0139] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0140] In a specific embodiment, the ambient temperature of the hot rolling roller is 60°C.

[0141] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0142] Example 5

[0143] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0144] Preparation of polymer-liquid metal mixed spinning solution:

[0145] The liquid metal is added into the polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0146] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0147] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0148] Preparation of fucoidan-liquid metal spinning solution:

[0149] Mixing a liquid metal gallium-indium alloy with a 2 wt % fucoidan solution at a weight ratio of 8:2 to obtain a first mixed solution;

[0150] The first mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a fucoidan-liquid metal spinning solution;

[0151] Preparation of sodium alginate-liquid metal spinning solution:

[0152] Mixing the liquid metal gallium-indium alloy with 2 wt % sodium alginate solution at a weight ratio of 8:2 to obtain a second mixed solution;

[0153] The second mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a sodium alginate-liquid metal spinning solution.

[0154] Specifically, in this step, the liquid metal undergoes high-speed stirring and shearing in a homogenizer, forming nano-scale droplets dispersed in the solution, and a polymer network dispersed on the metal surface and in the solution.

[0155] Preparation of polymer pregel fibers:

[0156] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0157] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0158] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0159] Post-treatment of polymer pre-gel fibers:

[0160] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0161] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0162] In a specific embodiment, the ambient temperature of the hot rolling roller is 60°C.

[0163] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0164] Compared with the conductive fibers prepared by encapsulating conductive fillers in polymer hollow tube fibers and coaxial wet spinning in the prior art, the metal gel fibers prepared by the metal gel fiber preparation method of the present scheme have the advantages of being conductive on the fiber surface and being directly used as electrodes.

[0165] Example 6

[0166] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0167] Preparation of polymer-liquid metal mixed spinning solution:

[0168] The liquid metal is added into the polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0169] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0170] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0171] Preparation of fucoidan-liquid metal spinning solution:

[0172] Mixing a liquid metal gallium-indium alloy with a 2 wt % fucoidan solution at a weight ratio of 9:1 to obtain a first mixed solution;

[0173] The first mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a fucoidan-liquid metal spinning solution;

[0174] Preparation of sodium alginate-liquid metal spinning solution:

[0175] Mixing the liquid metal gallium-indium alloy with 2 wt % sodium alginate solution at a weight ratio of 9:1 to obtain a second mixed solution;

[0176] The second mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a sodium alginate-liquid metal spinning solution.

[0177] Specifically, in this step, the liquid metal undergoes high-speed stirring and shearing in a homogenizer, forming nano-scale droplets dispersed in the solution, and a polymer network dispersed on the metal surface and in the solution.

[0178] Preparation of polymer pregel fibers:

[0179] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0180] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0181] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0182] Post-treatment of polymer pre-gel fibers:

[0183] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0184] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0185] In a specific embodiment, the ambient temperature of the hot rolling roller is 60°C.

[0186] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0187] Example 7

[0188] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0189] Preparation of polymer-liquid metal mixed spinning solution:

[0190] The liquid metal is added into the polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0191] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0192] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0193] Preparation of fucoidan-liquid metal spinning solution:

[0194] Mixing a liquid metal gallium-indium alloy with a 1 wt % fucoidan solution at a weight ratio of 9:1 to obtain a first mixed solution;

[0195] The first mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a fucoidan-liquid metal spinning solution;

[0196] Preparation of sodium alginate-liquid metal spinning solution:

[0197] Mixing the liquid metal gallium-indium alloy with 1 wt % sodium alginate solution at a weight ratio of 9:1 to obtain a second mixed solution;

[0198] The second mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a sodium alginate-liquid metal spinning solution.

[0199] Specifically, in this step, the liquid metal undergoes high-speed stirring and shearing in a homogenizer, forming nano-scale droplets dispersed in the solution, and a polymer network dispersed on the metal surface and in the solution.

[0200] Preparation of polymer pregel fibers:

[0201] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0202] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0203] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0204] Post-treatment of polymer pre-gel fibers:

[0205] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0206] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0207] In a specific embodiment, the ambient temperature of the hot rolling roller is 60°C.

[0208] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0209] Example 8

[0210] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0211] Preparation of polymer-liquid metal mixed spinning solution:

[0212] Liquid metal is added into a polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0213] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0214] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0215] Preparation of fucoidan-liquid metal spinning solution:

[0216] Mixing a liquid metal gallium-indium alloy with a 3 wt % fucoidan solution at a weight ratio of 9:1 to obtain a first mixed solution;

[0217] The first mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a fucoidan-liquid metal spinning solution;

[0218] Preparation of sodium alginate-liquid metal spinning solution:

[0219] Mixing the liquid metal gallium-indium alloy with 3 wt % sodium alginate solution at a weight ratio of 9:1 to obtain a second mixed solution;

[0220] The second mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a sodium alginate-liquid metal spinning solution.

[0221] Specifically, in this step, the liquid metal undergoes high-speed stirring and shearing in a homogenizer, forming nano-scale droplets dispersed in the solution, and a polymer network dispersed on the metal surface and in the solution.

[0222] Preparation of polymer pregel fibers:

[0223] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0224] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0225] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0226] Post-treatment of polymer pre-gel fibers:

[0227] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0228] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0229] In a specific embodiment, the ambient temperature of the hot rolling roller is 60°C.

[0230] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0231] Example 9

[0232] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0233] Preparation of polymer-liquid metal mixed spinning solution:

[0234] The liquid metal is added into the polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0235] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0236] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0237] Preparation of fucoidan-liquid metal spinning solution:

[0238] Mixing a liquid metal gallium-indium alloy with a 2 wt % fucoidan solution at a weight ratio of 9:1 to obtain a first mixed solution;

[0239] The first mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a fucoidan-liquid metal spinning solution;

[0240] Preparation of sodium alginate-liquid metal spinning solution:

[0241] Mixing the liquid metal gallium-indium alloy with 2 wt % sodium alginate solution at a weight ratio of 9:1 to obtain a second mixed solution;

[0242] The second mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a sodium alginate-liquid metal spinning solution.

[0243] Specifically, in this step, the liquid metal undergoes high-speed stirring and shearing in a homogenizer, forming nano-scale droplets dispersed in the solution, and a polymer network dispersed on the metal surface and in the solution.

[0244] Preparation of polymer pregel fibers:

[0245] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0246] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0247] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0248] Post-treatment of polymer pre-gel fibers:

[0249] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0250] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0251] In a specific embodiment, the ambient temperature of the hot rolling roller is 20°C.

[0252] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0253] Example 10

[0254] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0255] Preparation of polymer-liquid metal mixed spinning solution:

[0256] The liquid metal is added into the polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0257] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0258] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0259] Preparation of fucoidan-liquid metal spinning solution:

[0260] Mixing a liquid metal gallium-indium alloy with a 2 wt % fucoidan solution at a weight ratio of 9:1 to obtain a first mixed solution;

[0261] The first mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a fucoidan-liquid metal spinning solution;

[0262] Preparation of sodium alginate-liquid metal spinning solution:

[0263] Mixing the liquid metal gallium-indium alloy with 2 wt % sodium alginate solution at a weight ratio of 9:1 to obtain a second mixed solution;

[0264] The second mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a sodium alginate-liquid metal spinning solution.

[0265] Specifically, in this step, the liquid metal undergoes high-speed stirring and shearing in a homogenizer, forming nano-scale droplets dispersed in the solution, and a polymer network dispersed on the metal surface and in the solution.

[0266] Preparation of polymer pregel fibers:

[0267] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0268] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0269] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0270] Post-treatment of polymer pre-gel fibers:

[0271] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0272] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0273] In a specific embodiment, the ambient temperature of the hot rolling roller is 40°C.

[0274] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0275] Embodiment 11

[0276] like Figure 5 As shown, this embodiment discloses a method for preparing metal gel fiber, comprising the following steps:

[0277] Preparation of polymer-liquid metal mixed spinning solution:

[0278] The liquid metal is added into the polysaccharide polymer solution to obtain a mixed solution, and the mixed solution is evenly dispersed by a homogenizer to obtain a polymer-liquid metal spinning solution.

[0279] Specifically, the preparation of the polymer-liquid metal mixed spinning solution includes preparing a fucoidan-liquid metal spinning solution and preparing a sodium alginate-liquid metal spinning solution.

[0280] In a specific embodiment, the process of preparing the polymer-liquid metal mixed spinning solution is as follows:

[0281] Preparation of fucoidan-liquid metal spinning solution:

[0282] Mixing a liquid metal gallium-indium alloy with a 2 wt % fucoidan solution at a weight ratio of 9:1 to obtain a first mixed solution;

[0283] The first mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a fucoidan-liquid metal spinning solution;

[0284] Preparation of sodium alginate-liquid metal spinning solution:

[0285] Mixing the liquid metal gallium-indium alloy with 2 wt % sodium alginate solution at a weight ratio of 9:1 to obtain a second mixed solution;

[0286] The second mixed solution was stirred and sheared at a speed of 15000 rpm for 5 to 10 minutes at a temperature of 25° C. using a handheld homogenizer to obtain a sodium alginate-liquid metal spinning solution.

[0287] Specifically, in this step, the liquid metal undergoes high-speed stirring and shearing in a homogenizer, forming nano-scale droplets dispersed in the solution, and a polymer network dispersed on the metal surface and in the solution.

[0288] Preparation of polymer pregel fibers:

[0289] The fucoidan-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine through a spinneret and enters a coagulation bath for coagulation to form fucoidan pregel fibers. The extrusion speed of the pregel fibers is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0290] The sodium alginate-liquid metal spinning solution is placed in a spinning tank and allowed to stand for defoaming. The spinning solution passes through a wet spinning machine and a spinneret into a coagulation bath for coagulation to form a sodium alginate type pregel fiber. The extrusion speed of the pregel fiber is 2 mm / min to 6 mm / min, and the coagulation bath is a calcium chloride aqueous solution with a concentration of 0.01 M.

[0291] Specifically, in this step, the polymer-liquid metal composite microsphere droplets are gradually fixed in the polymer network.

[0292] Post-treatment of polymer pre-gel fibers:

[0293] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained fucoidan metal gel fiber was collected by a collecting roller.

[0294] The obtained fucoidan pregel fiber was repeatedly rolled by a hot roller for 3 times, and the obtained sodium alginate metal gel fiber was collected by a collecting roller.

[0295] In a specific embodiment, the ambient temperature of the hot rolling roller is 80°C.

[0296] In this step, as the moisture in the pre-gel fiber is gradually removed under the heating roller, the fiber volume shrinks, the internal polymer network gradually shrinks, the liquid metal composite microspheres fuse, and the oxide layer on the surface of the liquid metal breaks and flows to the microgel layer, penetrating each other to form an effective electronic conductive path, and is fixed in the fiber structure by the polymer network, obtaining a metal gel fiber with both high electrical and mechanical properties.

[0297] Compared with the prior art of directly coating the conductive filler on the fiber surface, which is easy to fall off when subjected to friction or scraping, the metal gel fiber prepared by the metal gel fiber preparation method of the present scheme has the advantages of uniform distribution of the conductive phase inside the fiber and strong stability.

[0298] The above schematically describes the invention and its implementation methods, which is not restrictive. Without departing from the spirit or basic features of the invention, the invention can be implemented in other specific forms. What is shown in the accompanying drawings is only one of the implementation methods of the invention. The actual structure is not limited to this, and any figure mark in the claims should not limit the claims involved. Therefore, if a person of ordinary skill in the art is inspired by it, without departing from the purpose of the invention, a structural method and an embodiment similar to the technical solution are designed without creativity, which should all fall within the scope of protection of this patent. In addition, the word "including" does not exclude other elements or steps, and the word "one" before the element does not exclude the inclusion of "multiple" elements. The multiple elements stated in the product claim can also be implemented by one element through software or hardware. The words first, second, etc. are used to indicate names, and do not indicate any specific order.

Claims

1. A method for preparing metal gel fiber, comprising the following steps: Preparing a polymer-liquid metal mixed spinning solution: adding liquid metal to a polysaccharide polymer solution to obtain a mixed solution, and uniformly dispersing the mixed solution with a homogenizer to obtain a polymer-liquid metal spinning solution; Preparation of polymer pregel fiber: placing the polymer-liquid metal spinning solution in a spinning tank and letting it stand to defoam, passing through a wet spinning machine through a spinneret and entering a coagulation bath at room temperature to coagulate, thereby forming a polymer pregel fiber; Post-treatment of polymer pre-gel fiber: The polymer pre-gel fiber is treated under a hot roller to remove the solvent and make the liquid metal interconnected, and the metal gel fiber is obtained by a collecting roller.

2. The method for preparing metal gel fiber according to claim 1, characterized in that: The polymer-liquid metal mixed spinning solution is ultrasonically dispersed into nano-microsphere droplets in the polymer aqueous solution by a homogenizer. The polymer chains form a physically cross-linked network and adsorb on the surface of the liquid metal to form a microgel shell. The polymer undergoes coordination and solidification in the coagulation bath, and the microsphere droplets are fixed in the polymer network.

3. The method for preparing metal gel fiber according to claim 1, characterized in that: The preparation of polymer-liquid metal mixed spinning solution includes the preparation of fucoidan-liquid metal spinning solution and the preparation of sodium alginate-liquid metal spinning solution.

4. The method for preparing metal gel fiber according to claim 3, characterized in that: The steps of preparing the fucoidan-liquid metal spinning solution are: mixing the liquid metal gallium-indium alloy with 1wt% to 3wt% of the fucoidan solution in a weight ratio of (6:4) to (9:1) to obtain a first mixed solution; The first mixed solution was stirred and sheared at a temperature of 25° C. using a handheld homogenizer at a speed of 8000 rpm to 15000 rpm for 5 to 10 minutes to obtain a fucoidan-liquid metal spinning solution.

5. The method for preparing metal gel fiber according to claim 3, characterized in that: The steps of preparing the sodium alginate-liquid metal spinning solution are: mixing the liquid metal gallium-indium alloy with 1wt% to 3wt% of the sodium alginate solution in a weight ratio of (6:4) to (9:1) to obtain a second mixed solution; The second mixed solution was stirred and sheared for 5 to 10 minutes at a speed of 8000 to 15000 rpm using a handheld homogenizer at a temperature of 25° C. to obtain a sodium alginate-liquid metal spinning solution.

6. The method for preparing metal gel fiber according to claim 1, characterized in that: The preparation of polymer pregel fiber includes the preparation of fucoidan pregel fiber and the preparation of sodium alginate pregel fiber.

7. The method for preparing metal gel fiber according to claim 6, characterized in that: The steps for preparing fucoidan pregel fiber are as follows: placing the fucoidan-liquid metal spinning solution into a spinning tank and letting it stand to defoam; the spinning solution passes through a wet spinning machine through a spinneret and enters a 0.01M calcium chloride coagulation bath at room temperature to coagulate, thereby forming fucoidan pregel fiber.

8. The method for preparing metal gel fiber according to claim 6, characterized in that: The steps of preparing sodium alginate pregel fiber are as follows: placing sodium alginate-liquid metal spinning solution into a spinning tank for standing and defoaming, and the spinning solution passes through a wet spinning machine through a spinneret into a 0.01M calcium chloride coagulation bath at room temperature for coagulation to form sodium alginate pregel fiber.

9. The method for preparing metal gel fiber according to claim 1, characterized in that: In the process of post-processing the polymer pregel fiber, the polymer pregel fiber is repeatedly rolled by a hot roller for 3 times, and the ambient temperature of the hot roller is 20-80°C.

10. The metal gel fiber prepared according to the method for preparing metal gel fiber according to any one of claims 1 to 9, characterized in that: including liquid metals and polymer networks; The liquid metal is the conductive phase of the metal gel fiber, which runs through the polymer network and forms a continuous conductive structure; The polymer network is a three-dimensional porous nano-network structure and is evenly distributed in the metal gel fibers.

Citation Information

Patent Citations

  • Flexible liquid metal / seaweed composite fiber and preparation method thereof

    CN115233335A

  • Double-conductive-network metal gel conductive fiber and preparation method and application thereof

    CN117552126A